Evidence for localised HIV related micro-epidemics associated with the decentralised provision of antiretroviral treatment in rural South Africa: a spatio-temporal analysis of changing mortality patterns (2007-2010) - Paul Mee; Mark A. Collinson; Sangeetha Madhavan; Elisabeth Dowling Root; Stephen M. Tollman; Peter Byass; Kathleen Kahn (Edinburgh University Global Health Society, 2014)
In this study we analysed the spatial and temporal changes in patterns of mortality over a period when antiretroviral therapy (ART) was rolled out in a rural region of north-eastern South Africa. Previous studies have identified localised concentrated HIV related sub-epidemics and recommended that micro-level analyses be carried out in order to direct focused interventions.